From Centrally-Planned to Market Economies : The Road from CPE to PCPE - Frenkel, Jacob (IMF Working Papers; Working Paper ;, 1991)
This paper deals with the early stages of transformation of centrally-planned economies (CPEs) into market economies during which expectations play a key role. It focuses on the transitional phase during which the economy is not any more a CPE but has not yet become a market economy. During this phase the economy is referred to as a 'previously centrally-planned economy' (PCPE). A simple model is developed to analyze the consequences of expected price liberalization. The CPEs undergoing transformation lack depth and breadth of financial markets. The analysis illustrates the benefits from an early development of such markets. It demonstrates the cost of a fine-tuning strategy and the benefits from a quick implementation of price reform. The paper also examines means to reduce 'liquidity overhang,' and shows that they involve taxation of one form or another. The consequences of privatization are analyzed and the benefits from an early development of an effective tax system highlighted.